Muslim Traveller Halal Food Consumption Attitude and Behavioral Intentions of Indonesian Muslim - Amelia (Halal Tourism and Pilgrimage, 2021)
The demand for a Muslim friendly tourism industry has gained momentum from increasing the number of Muslim travelers globally. This paper aims to examine the role of religiosity in Muslim tourists—attitudes and behavior of consuming halal food when traveling to non-Muslim destinations. A total of 100 respondents participated in this study via an online survey. This study uses partial least square structural equation modeling (PLS-SEM) to assess survey measurements and hypothesis testing. This study confirms that Muslim tourists' halal consumption attitude is highly dependent on the level of religiosity, subjective norms, and perceived control behavior. Besides, this study's results provide evidence that consumption attitudes mediate the relationship between subjective norms and intention to consume halal food products when traveling abroad. This study highlights a critical aspect of the growing Muslim market who travels for leisure with an urge to adhere to Islamic teachings and their religiosity. Non-Muslim destination marketers must adjust their marketing strategies and consider promoting Islamic dietary rules when planning their travel packages. This study is one of the few studies that focus on Muslim friendly tourism and the role of religiosity in Muslim tourists' consumption behavior of Halal food. This study confirms that the planned behavior model theory can explain the attitude of Muslim tourists' consumption of halal food when traveling to non-Muslim destinations.